Alterations in circulating markers in HIV/AIDS patients with poor immune reconstitution: Novel insights from microbial translocation and innate immunity - Xiao, Qing; Yu, Fengting; Yan, Liting; Zhao, Hongxin; Zhang, Fujie (Frontiers in Immunology, 2022)
After long-term anti-retroviral therapy (ART) treatment, most human immunodeficiency virus (HIV)/Acquired Immure Deficiency Syndrome (AIDS) patients can achieve virological suppression and gradual recovery of CD4+ T-lymphocyte (CD4+ T cell) counts. However, some patients still fail to attain normal CD4+ T cell counts; this group of patients are called immune non-responders (INRs), and these patients show severe immune dysfunction. The potential mechanism of poor immune reconstitution (PIR) remains unclear and the identification of uniform biomarkers to predict the occurrence of PIR is particularly vital. But limited information is available on the relationship between circulating markers of INRs and immune recovery. Hence, this review summarises alterations in the intestine microbiota and associated markers in the setting of PIR to better understand host-microbiota-metabolite interactions in HIV immune reconstitution and to identify biomarkers that can predict recovery of CD4+ T cell counts in INRs.